2001
DOI: 10.4049/jimmunol.167.12.6983
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antigen in the Localization of Naive, Acutely Activated, and Memory CD8+ T Cells to the Lung During Influenza Pneumonia

Abstract: The role of Ag in the recruitment and localization of naive, acutely activated, and memory CD8+ T cells to the lung during influenza infection was explored using TCR-transgenic (Tg) mice. Naive, Thy1.2+CD8+ OT-I TCR-Tg cells were primed and recruited to the lung after transfer into congenic Thy1.1+ recipients challenged with a genetically engineered influenza virus (influenza A/WSN/33 (WSN)-OVAI) containing the Kb restricted OVA257–264 epitope (siinfekl) in the viral neuraminidase stalk. However, if the transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
129
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(139 citation statements)
references
References 67 publications
9
129
1
Order By: Relevance
“…We believe the cells are lost by apoptosis or phagocytosis, because previous studies have shown that lung airway memory T cells are unable to migrate from the lung airways back into the circulation (7,37). These observations extend previous studies in the field by distinguishing the relative contributions of resident memory cells, recruitment, and proliferation to the expansion of memory cells in the lung airways induced by heterologous virus infections (14,19).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We believe the cells are lost by apoptosis or phagocytosis, because previous studies have shown that lung airway memory T cells are unable to migrate from the lung airways back into the circulation (7,37). These observations extend previous studies in the field by distinguishing the relative contributions of resident memory cells, recruitment, and proliferation to the expansion of memory cells in the lung airways induced by heterologous virus infections (14,19).…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies have shown that respiratory virus infections induce an increase in the numbers of heterologous memory CD8 ϩ T cells in the lung or lung airways (14,19,28). However, it was not clear whether this reflected local proliferation or recruitment of cells from other sites.…”
Section: Sendai Virus Specific Memory Cells In the Lung Airways Incrementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Ag-nonspecific memory CD8 ϩ T cells have been shown to migrate to the lungs after respiratory infection with RSV, influenza virus, and Sendai virus (33)(34)(35). However, nonspecific recruitment of irrelevant memory CD8 ϩ T cells to the inflamed lungs is an unlikely explanation for our findings.…”
Section: Discussioncontrasting
confidence: 51%
“…Non-lymphoid Sites following Adoptive Transfer-Our laboratory (6) as well as others (7,10,11,14,18) have demonstrated that T cell effectors activated by infection or antigen in adjuvant can migrate to the site of inflammation where they secrete cytokines, display cytolytic activity, and participate in pathogen clearance. To analyze the regulation of CD4 ϩ T cell subset recruitment to non-lymphoid sites, we used a standard in vitro activation protocol to generate Th1 and Th2 effector cells that produced interferon-␥ and IL-4, respectively (15,17,19).…”
Section: Th1 and Th2 Effector Cells Migrate To Both Lymphoid Andmentioning
confidence: 99%